Great Soul of Siberia : passion, obsession, and one man's quest for the world's most elusive tiger - Park, Sooyong Cineasta; 박수용 (Berkeley Greystone Books, 2015)
In The Great Soul of Siberia, renowned tiger researcher Sooyong Park tracks three generations of Siberian tigers living in remote southeastern Russia. Reminiscent of the way Timothy Treadwell (the so-called Grizzly Man) immersed himself in the lives of bears, Park sets up underground bunkers to observe the tigers, living thrillingly close to these beautiful but dangerous apex predators. At the same time, he draws from twenty years of experience and research to focus on the Siberian tigers' losing battle against poaching and diminishing habitat. Over the two years of his harrowing stakeout, Park's poignant and poetic observations of the tigers draw a fiercely compassionate portrait of these elusive, endangered creatures.tomade de:https://www.bookdepository.com/Great-Soul-Siberia-Sooyong-Park/9781771641135
Part 1. Bloody Mary. Tigress in the basin of skeletons -- The traveling base camp -- The spirit of the Sikhote-Alin -- Fishing tiger -- Part 2. Amba, god of the forest. A tiger leaves his mark -- Temu, the spirit of storm -- Deer hunting in the fog -- Survival-of-the-fittest cub -- Tiger family on the beach -- People who worship tigers -- Part 3. To meet, and to say goodbye. Hotel construction -- Cold weather, green pines -- The challenge and response of the Ussuri Forest -- White Moon, White Snow, White Sky -- Between solitude and passion -- Merry Christmas, Bloody Mary -- By the skin of tiger teeth -- Tiger for sale -- White Snow and White Sky's dispute -- Season of melting snow -- Part 4. New generation. Commotion in the forest -- Tigers and azaleas -- Chance encounter -- Night of beasts -- Chrysanthemums -- Part 5. Another winter. Hansel and Gretel -- The future of Ussuri Forest -- The great king comes home -- Raising Hansel and Gretel -- Requiem for the fading -- The grief of the living -- The tiger lives on -- Epilogue : diamond dust.
La obsesiva búsqueda de un documentalista por el tigre siberiano en peligro de extinción.
Publicado bajo el apoyo del Instituto de Traducción de Literatura de Corea (LTI Corea)
Keywords: Park, Sooyong -- Filmmaker -- Travel; Tigres -- Rusia (Lejano oriente); SOUL -- SIBERIA -- 시베리아 -- 영혼 -- 한국도서번역 -- 한국문학번역원; Literatura coreana; Tigres siberianos